Vocational training and British economic performance : a further instalment of the 'British labour problem'? - Cutler, Tony [Verfasser] (My University, 1992)
"This paper compares two influential 'explanations' of Britain's economic problems - one, the British Labour Problem, points to the attitudes of British workers and their unions as the cause of poor productivity, the other, the British Training Problem, points to the low level and poor quality of vocational training in the UK as the source of economic ills. The paper argues that, despite apparent differences, the two discourses are very similar, so much so that it is valid to see arguments about the relation of vocational training and economic performance as a new instalment of the British Labour Problem. Just as the labour problem was a bogus characterization of the causes of Britain's problems in the 1980s and led to unhelpful policies, so the current preoccupation with training promises to play an analogous role in the 1990s." (author's abstract) ((en)) Der Beitrag befasst sich mit zwei bedeutenden Erklärungsansätzen zu den wirtschaftlichen Problemen Grossbritanniens. Die Ursachen für die mangelnde Produktivität werden dabei in der Haltung der britischen Arbeitnehmer und ihrer Gewerkschaften (zu geringes Arbeitstempo, Widerstand gegenüber dem technischen Wandel ...) bzw. in der schlechten Ausbildungsqualität gesehen. Der Autor vergleicht die beiden Ansätze und die daraus abgeleiteten politischen Implikationen der 80er und 90er Jahre. (IAB)
Berufsausbidung und Leistungsfähigkeit der britischen Wirtschaft
Keywords: G 2.3.3 Arbeitsformen, Techniken; S 3.5.4.1 Gewerkschaften; G 1.2.3.1 Potenziale; Berufsausbildung; Produktivität; Einflussfaktor; Arbeiter; Kooperation; Gewerkschaft; Qualifikationsniveau